Mao. 23 - Takahashi, Rumiko, 1957-; Roman, Annette (VIZ Media, LLC, 2026)
When Nanoka is transported back in time to a supernatural early 20th century, she gets recruited by aloof exorcist Mao. What thread of fate connects them? Together, they seek answers...and kick some demon butt along the way!The battle of the Goko clan apprentices reignites, pitting Mao against enemies and allies alike! Then, Diago's murderer is finally revealed, but will his reanimated body ever regain its soul? Plus, our friends investigate a monstrous patriarch who is terrorizing his own family. And Nanoka suffers a great loss...